Utilizing information communication technologies for facilitating business education instructions in Nigeria - Isiyaku, Dauda Dansarki; Mohd Ayub, Ahmad Fauzi; Abdul Kadir, Suhaida (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
Owing to the continuous increase in human knowledge and technological sophistication, it has become obvious that in order to cope with global standards, school instructions must be facilitated by the use of Information Communications Technologies. However, while some regions of the world are already transformed by remarkable ICT sophistications in almost all their sectors, especially education; it is ironical that some other regions are yet to begin. Hence, this paper attempts to highlight on the status of business education with regard to ICT adoption and utilization in Nigeria.